CRISPR‐Cas system for biomedical diagnostic platforms. Issue 3 (25th July 2020) - Wang, Zhen; Cui, Wenguo
Abstract: Clustered short palindrome repeats with regular intervals, abbreviated as CRISPR, and functions as a self‐defense system for prokaryotes, detecting particular pathogenic nucleic acid, interfering with the functions of exoteric DNA, and protecting them against foreign invaders. In recent years, CRISPR has attracted increasing interests in the in vitro diagnostic field because of its inherent allele specificity, which is one of the critical factors for the successful application of this technology in the development of high‐precision treatment and diagnosis. Herein, this review article aims to provide an overview of CRISPR‐CRISPR associated proteins (Cas) based biomedical diagnostics, including the biological mechanism, biomaterials, and applications. This paper first briefly introduces the development history and biological characteristics of the CRISPR‐Cas system, and then summarizes the application status and development trend of the CRISPR‐Cas system in the detection and identification of particular pathogens, specifically displaying a brilliant prospect in the most recent outbreak of novel coronavirus (formerly named 2019‐nCoV). Moreover, its potential diagnostic power in oncogene mutations and single nucleotide variations detecting are assembled. Finally, we discuss challenges and future prospects of CRISPR‐Cas system based diagnostic platforms in biomedicine, hoping to further inspire the development of biomedical diagnostics. Abstract : CRISPR‐Cas–based diagnostic tests have been the frontline of various pathogenic factors detection including virus, bacterium, fungus, spirochete, chlamydia, and parasite, during daily practice or pandemic, as well as have the potential to screen for carcinogenic mutations and genetic diseases. The CRISPR‐Cas–based diagnostics open a new window in the clinical laboratory with remarkable convenience, sensitivity, and specificity, bringing forth revolutionized diagnostic development.